Model Sikap Konsumen pada Kegiatan Cause Related Marketing - , Singgih Santoso, SE.,MM. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Company support of social cause, called cause related marketing (CRM), has experienced extraordinary growth and has become a common practice for many marketing programs. Using signalling theory, this study empirically tests a formation of attitude toward alliance model, which consists of impact of attitude toward brand, attitude toward cause, product fit, and brand fit on attitude toward CRM, and evaluate the impact of attitude toward CRM on purchase intention. 2 x 2 factorial design experiment with the use of experience-product was conducted, and experimental results indicate many interest findings